Dynamic economics and the recursive approach - Rojas, Germán (Estudios Económicos de El Colegio de México, 1991)
This paper offers a detailed review of the book Recursive Methods and Economic Dynamic s by Nancy L. Stokey and Robert E. Lucas (with Edward C. Prescott), Cambridge, Harvard University Press, 1989.